Ozone (03)-Oxygen mixture therapy inhibits endometrial implant growth - Aktun, H. L.; Atilgan, R.; Karaca, N.; Acet, M.; Yorgunlar, B.; Can, B.; Irban, A. (C I C-Edizioni Int Srl, 2016)
[Abstract Not Available]
Keywords: Factor-Kappa-B; Expression; Balance